The Influence of Governance, Economic Growth, and Foreign Direct Investment on Tax Ratios in Southeast Asian Countries - Yuliani Rahayu; Einde Evana; Tri Joko Prasetyo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to examine the influence of Government Effectiveness, Regulatory Quality, Control of Corruption, Economic Growth, and Foreign Direct Investment on Tax Ratios in Southeast Asian Countries. The population in this study was all ASEAN countries, totaling 11 countries. The research sample was taken using a technique of non-probability sampling. The method used is the panel data technique which is a combination of time series and cross section data. The cross-section data in this research is ASEAN country data with a time series for the period 2010 to 2022 from the World Bank. The analysis technique used is the classical assumption test, chow test, Hausman test, and test Lagrange multiplier. The research results show that government effectiveness, control of corruption, economic growth, and foreign direct investment influence the tax ratio. Meanwhile, regulatory quality does not have a significant effect on the tax ratio.